1982
DOI: 10.1002/1097-0142(19821201)50:11<2406::aid-cncr2820501127>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Tissue ferritin concentration in carcinoma of the breast

Abstract: Ferritin concentration was measured in cytosol extracts of 44 mammary carcinomas and 14 benign breast tissues. A six‐fold difference was observed (mean, 364.6 ± 223.3 ng/mcp in malignant tissue versus mean, 60.2 ± 42.1 ng/mcp in benign tissue P < 0.001). Thirty‐five malignant tissue specimens were reviewed independently by a pathologist without knowledge of their ferritin contents. Higher concentrations of ferritin were present in malignancies with greater degrees of epithelial proliferation and plemorphism su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 29 publications
2
52
0
1
Order By: Relevance
“…174 However, subsequent evaluations of ferritin levels in tumor tissue itself have revealed a complex, perhaps disease-specific picture: for example, in some cases such as colon cancer, 175 testicular seminoma, 176 and breast cancer, 177,178 increases in ferritin in tumor tissue versus comparable normal tissue have been reported; in other cases, including liver cancer, a decrease in ferritin is seen. 179 New forms of ferritin may be involved in certain situations: Moroz and coworkers have described a novel isoform of ferritin that is elevated in the serum of patients with neoplastic breast disease as well as during pregnancy and HIV infection.…”
Section: Oncogenes Cancer and Ferritinmentioning
confidence: 99%
“…174 However, subsequent evaluations of ferritin levels in tumor tissue itself have revealed a complex, perhaps disease-specific picture: for example, in some cases such as colon cancer, 175 testicular seminoma, 176 and breast cancer, 177,178 increases in ferritin in tumor tissue versus comparable normal tissue have been reported; in other cases, including liver cancer, a decrease in ferritin is seen. 179 New forms of ferritin may be involved in certain situations: Moroz and coworkers have described a novel isoform of ferritin that is elevated in the serum of patients with neoplastic breast disease as well as during pregnancy and HIV infection.…”
Section: Oncogenes Cancer and Ferritinmentioning
confidence: 99%
“…Iron can cause oxidative tissue damage by catalyzing HaberWeiss and Fenton reactions that convert hydrogen peroxide (H 2 O 2 ) to free radicals (9)(10)(11)(12). In women, neoplastic breast tissue contains higher levels of iron and ferritin compared with normal tissue (13,14), and rats fed excess iron develop earlier and more numerous mammary tumors (15), whereas those fed iron-deficient diets are protected (16). Currently, some epidemiologic studies support a role for excessive dietary iron intake and risk of total cancers (17)(18)(19) as well as risk of lung and colon cancers (17,(20)(21)(22)(23), but there are few data on relationships with breast cancer (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with solid tumours, such as pancreatic carcinoma, lung cancer and hepatoma, there is a particularly high incidence of elevated plasma ferritin, and in patients with breast cancer, with metastasis, ferritin plasma concentrations are commonly elevated (Worwood, 1982). It is of interest that ferritin levels in breast cancer are not only raised in the plasma, but also in breast tissue (Ionescu et al, 2006;Weinstein et al, 1982). Squamous cell carcinoma of the head and neck is marked by increased plasma ferritin concentrations, which remains high in patients with a poor prognosis in contrast to patients with a favourable prognosis (Maxim & Veltri, 1986).…”
Section: H-subunit Rich Ferritins and Cancermentioning
confidence: 99%
“…It is suggested that an increase in the labile iron pool plays a role, since depletion of the labile iron pool and a decrease in ROS suppress the migration of tumour cells (Zhang et al, 2009). In contrast, up-regulation of intracellular H-subunit rich ferritins has been shown in several studies (Elliot et al, 1993;Shpeleva et al, 2011;Weinstein et al, 1982). In the study by Shpeleva et al, involving human breast cancer, an increase in the expression of the H-subunit and Lsubunit intracellular levels of ferritin was associated with a decrease in the labile iron pool (Shpeleva et al, 2011).…”
Section: H-subunit Rich Ferritins and Cancermentioning
confidence: 99%
See 1 more Smart Citation